Targeting the BspC-vimentin interaction to develop anti-virulence therapies during Group B streptococcal meningitis. - Haider S Manzer; Ricardo I Villarreal; Kelly S Doran (PLoS Pathogens, 2022)
Bacterial infections are a major cause of morbidity and mortality worldwide and the rise of antibiotic resistance necessitates development of alternative treatments. Pathogen adhesins that bind to host cells initiate disease pathogenesis and represent potential therapeutic targets. We have shown previously that the BspC adhesin in Group B Streptococcus (GBS), the leading cause of bacterial neonatal meningitis, interacts with host vimentin to promote attachment to brain endothelium and disease development. Here we determined that the BspC variable (V-) domain contains the vimentin binding site and promotes GBS adherence to brain endothelium. Site directed mutagenesis identified a binding pocket necessary for GBS host cell interaction and development of meningitis. Using a virtual structure-based drug screen we identified compounds that targeted the V-domain binding pocket, which blocked GBS adherence and entry into the brain in vivo. These data indicate the utility of targeting the pathogen-host interface to develop anti-virulence therapeutics.